A new model for viscous oil-water eccentric core annular flow in horizontal pipes. (February 2022) - Sun, Jie; Guo, Liejin; Fu, Jiqiang; Jing, Jiaqiang; Yin, Xiaoyun; Lu, Yingda; Ullmann, Amos; Brauner, Neima
Highlights: A new mechanistic model for viscous oil-water eccentric CAF in horizontal pipes was developed. The model enables predicting essential flow characteristics of oil-water core flows over a wide range of operational conditions. The proposed model shows a better performance than other models available in literature. The model offers the flexibility of treating cases where the properties of the lubricating phase are different in the two regions. Abstract: Eccentric core-annular flow is encountered in water-lubricated transport of highly viscous oil in horizontal pipes. The core eccentricity results from the tendency of the phases to stratify due to a buoyant force that results from their different densities, whereby a shape of a circular core may not be maintained. To model such a flow configuration, a new three-zone model is proposed based on the Two-Fluid approach. The model's performance was examined by comparing its predictions with a large data set of pressure gradient and water holdup values obtained under different experimental conditions. It is shown that the proposed model enables better agreement with the data compared to other models available in the literature. Thus, the proposed approach appears to be a useful framework for modeling viscous oil-water eccentric core-annular flows. It can also be applied for other types of Newtonian/non-Newtonian or non-Newtonian/non-Newtonian liquid-liquid core flows encountered in industrial applications.